The effect of a direct-fed microbial and dietary fat inclusion on performance and energy metabolism in broiler chicks and turkey poults - Samantha Black; Adam Fahrenholz; Jesse Grimes (German Journal of Veterinary Research)
Two battery trials were conducted to determine the effects of dietary direct-fed microbial (DFM) and dietary fat inclusion on broiler chick and turkey poult performance and dietary apparent metabolizable energy, nitrogen corrected (AMEn) when fed corn, wheat, and soy diets. For both experiments, a 2 x 2 factorial experimental design was used with supplemental fat at low (1%, LF) or high (6%, HF) levels and DFM inclusion (0 or 0.91 kg/ton) as main effects. Dietary treatments were randomly assigned to 72 cages of birds and fed to 21 d. Growth performance was measured weekly and cecal contents were collected for volatile fatty acid (VFA) analysis on d 21. Fat supplementation resulted in increased body weight gain (BWG) in both broilers and turkeys. Specifically, in LF diets, DFM inclusion resulted in increased BWG compared to the non-DFM treatments. Cumulative feed conversion ratio (FCR) was improved in HF treatments and in the LF with DFM treatment compared to the LF with no DFM. In both trials, as expected, feeding HF diets resulted in increased AMEn. However, the DFM inclusion resulted in a greater uplift in AMEn in LF diets for both broilers and turkeys. Cecal VFA concentrations were not impacted by diet in either trial, and thus the impact on DFM on VFA production remains uncertain. In conclusion, the performance of broiler chicks and turkey poults was improved by DFM inclusion in reduced fat diets which was associated with increased energy digestibility as measured by AMEn.